2017
DOI: 10.1021/acs.orglett.6b03683
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Catalyst-Directed Dynamic Kinetic Diastereoselective Acylation of Anomeric Hydroxyl Groups and a Controlled Reduction of the Glycosyl Ester Products

Abstract: A catalytic method is developed for the diastereoselective acylation of the anomeric hydroxyl group in diverse carbohydrates to form either α- or β-anomeric esters. While exclusive formation of the β-isomer was observed in most sugar substrates with one enantiomer of the chiral catalyst, moderate to high α-selectivity was obtained by using the other enantiomer of the chiral catalyst. The resulting α- and β-anomeric esters have very different reactivity toward a reduction reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Recently, n –cation interactions between an oxygen lone pair and a positively charged heterocyclic moiety of an organocatalytic intermediate were implicated by Tang and co-workers as the key selectivity-determining factor in site-selective acylation of carbohydrates and enantioselective dynamic kinetic acylation of 2-chromanols . Furthermore, a recent review demonstrated that this paradigm of directing n –cation noncovalent interactions was also responsible for inducing diastereoselectivity in dynamic kinetic acylation of anomeric hydroxyls in carbohydrates and their precursors, reported earlier by the same group …”
mentioning
confidence: 81%
“…Recently, n –cation interactions between an oxygen lone pair and a positively charged heterocyclic moiety of an organocatalytic intermediate were implicated by Tang and co-workers as the key selectivity-determining factor in site-selective acylation of carbohydrates and enantioselective dynamic kinetic acylation of 2-chromanols . Furthermore, a recent review demonstrated that this paradigm of directing n –cation noncovalent interactions was also responsible for inducing diastereoselectivity in dynamic kinetic acylation of anomeric hydroxyls in carbohydrates and their precursors, reported earlier by the same group …”
mentioning
confidence: 81%
“…Considering that the axial hydroxyls in a carbohydrate scaffold are in general less reactive than the equatorial ones, it is remarkable this reaction could override such reactivity bias and modify the axial 2-OH of 4 selectively. In 2017, the Tang group 47,50,51 reported a catalyst-controlled, site-divergent acylation of carbohydrates with benzotetramisole-based catalysts 52,53 (11 to 12 or 12 0 via 14; Figure 1D). It is proposed that the favorable interaction between the lone pair electrons on OR 0 of the nucleophile and the cationic center in the electrophile (cf.…”
Section: The Bigger Picturementioning
confidence: 99%
“…[13] Tang and co-workers reported the dynamic kinetic diastereoselective acylation of lactols through chiral isothiourea catalytic reactions. [14] We recently disclosed a carbene-catalyzed enantioselective modification of carboxylic acids for asymmetric access to optically enriched acetal products (Figure 1 b). [15] Here we disclose a new approach for enantiomeric access to acylated hydroxyphthalides by a carbene-catalyzed dynamic kinetic resolution (DKR) process (Figure 1 b).…”
mentioning
confidence: 99%